THE FREQUENCY OF THE SPREAD OF FUNCTIONAL CONSTIPATION IN CHILDREN IN THE BUKHARA REGION (World Bulletin of Public Health, 2022)
According to various authors, the prevalence of constipation among the adult population of highly developed countries varies from 4 to 45%, and among children - from 0.7 to 34%. In the UK, according to researchers, 34% of children aged 4 to 7 years suffered from constipation. According to research data published in recent years in the Russian Federation (RF), the incidence of constipation in children is about 25-30%. It is believed that 10 to 25% of children suffer from constipation, but its true prevalence in children is unknown due to the low prevalence of parents in this regard to the doctor.
Keywords: Children; Constipation; Defecation; Fecal Stones.